Cetane number, derived cetane number, and cetane index: When correlations fail to predict combustibility. (1st April 2021) - Luning Prak, Dianne; Cooke, Jay; Dickerson, Terrence; McDaniel, Andy; Cowart, Jim
Graphical abstract: Highlights: Derived cetane number (DCN), cetane number (CN), and cetane index (CI) compared. Aromatic compounds have similar DCNs and differing CIs. Isoalkanes have varying DCNs and similar CIs. Fuels found to contain up to 47% isoalkanes. Reference and surrogate fuels with high isoalkanes had CI > 43 and CN < 42. Abstract: Cetane number (CN) and derived cetane number (DCN) are used to quantify fuel ignitability in a diesel engine, with minimum standards set by various countries. Cetane index (CI), which is an empirical correlation based on density and distillation curve temperatures, is allowed in place of CN and DCN in some fuel specifications. In this study, comparisons were made between the CIs and DCNs or CNs of various fuel-related systems to determine where the correlation predictions fail. Petroleum- and bio-based fuels, pure components, mixtures of pure components with jet fuel, primary reference fuels, secondary reference fuels, and surrogate mixtures were all examined. For pure components, CIs capture the general trends of linear and cycloalkanes but not those of aromatic compounds and isoalkanes. Jet fuels doped with isoalkanes produced mixtures where CIs overestimated DCNs. No overestimation was found when doping with aromatic compounds. The presence of isoalkanes in a bio-based fuel from iso -butanol, surrogate fuel mixtures, and primary (PRF) and secondary reference fuels also produced CIs that overestimated CNs, while PRFs with aromatic 1-methylnapthalene had CI values that underestimated CNs. This analysis shows that isoalkanes contribute to CIs that overpredict CN and DCN. Petroleum-based fuels examined here contain between 15 and 47% iso -alkanes. The fuels with higher isoalkane concentration may have CIs that overpredict the CNs producing specification "passes" where CNs would fail. Such fuels may encounter problems under certain diesel engine operating conditions, such as cold-starts.